National Organization for the Professional Advancement of Black Chemists and Chemical Engineers newsletter, July 1977 (National Organization for Black Chemists and Chemical Engineers, 1977)
Issue number 6 of the National Organization for the Professional Advancement of Black Chemists and Chemical Engineers (NOBCChE) newsletter, published July 1977.
Keywords: Newsletters; African American chemists; African American engineers; Chemical engineers; Chemists; National Organization for Black Chemists and Chemical Engineers